Intelligent technologies for interactive entertainment : 9th International Conference, INTETAIN 2017, Funchal, Portugal, June 20-22, 2017, Proceedings /: 9th International Conference, INTETAIN 2017, Funchal, Portugal, June 20-22, 2017, Proceedings. (2018) - Unknown
No abstract available